Research and development in manufacturing: Companies performing better than ever - Alexander Eikelpasch (DIW Economic Bulletin, 2015)
In 2008 and 2009, during the economic crisis, Germany's industrial enterprises invested considerably less in research and development (R&D). From 2010 to 2013, investments increased markedly again by an annual growth rate of 6.8 percent. This increase can be partly traced back to the process of catching-up after the crisis. Considering the period 2008 to 2013 research expenditures increased by annually 3.2 percent. Spending related to added value also increased. The research-intensive sectors were primarily responsible for these increases. The larger firms with 250 or more employees expanded their R&D spending considerably, while small and medium-sized enterprises (20 to 249 employees) reduced investment slightly - possibly also because higher government R&D funding during the crisis was scaled back after 2012. Consequently, R&D spending has not increased across the board. Overall, however, manufacturing in Germany is heading in the right direction with strong R&D growth putting it on a more solid footing than in other European countries.
Keywords: O31; L60; D24; 330; Research and Development; Manufacturing; Business Cycle